PEACEFUL END OF LIFE IN LATE-STAGE CANCER PATIENTS: CONCEPT ANALYSIS BY WALKER AND AVANT - Anjarwani, Sushanty; wahyuni; Vranada, Aric; Aisah, siti (Nurse and Health: Jurnal Keperawatan, 2025)
Background:The increasing number of malignant cancer patients makes end-of-life care an inseparable element of nursing services. The concept of peaceful end-of-life is very popular , but it is complex and abstract. Understanding the concept of peaceful end-of-life helps professional nurses improve the quality of care outcomes for patients suffering from terminal or life-threatening illnesses.  Objective:The researcher's goal was to clarify and clarify the understanding of the concept of peaceful end-of-life in end-stage cancer patients using the approach of Walker and Avant (2005).  Methods: This concept analysis was conducted using the eight steps proposed by Walker and Avant. Results:Attributes of peaceful end-of-life in advanced cancer patients include: freedom from pain, a feeling of comfort, acceptance of the disease, and the presence and support of those closest to them. Antecedents, consequences, and empirical referents are explained. Model cases, related cases, threshold cases, and conflicting cases are illustrated to further clarify the concepts.  Conclusion: Four attributes are interconnected and play a role in forming a complete state of peace for terminal cancer patients according to Walker & Avant's analytical approach.